2015
DOI: 10.5194/amt-8-2463-2015
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the poke-flow technique combined with simulations of fluid flow for determining viscosities in samples with small volumes and high viscosities

Abstract: Abstract. Viscosity in particles consisting of secondary organic material (SOM) has recently become an area of research focus, since information on viscosity is needed to predict the environmental impacts of SOM particles. Recently Renbaum-Wolff et al. (2013a) developed a poke-flow technique that was combined with simulations of fluid flow to constrain the viscosities of SOM samples of 1-5 mg mass, roughly the maximum that may be collected from environmental chambers or flow tubes on a reasonable timescale. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 52 publications
5
77
0
Order By: Relevance
“…The qualitative method of poking an inorganic particle to determine its phase (i.e., solid or liquid) was introduced by Murray et al (2012). Renbaum-Wolff et al (2013a) and Grayson et al (2015) expanded on this method by measuring the characteristic flow time of a material after poking and extracting viscosity information from simulations of fluid flow. Briefly, supermicron toluene-derived SOM particles deposited on a hydrophobic substrate (toluene 5-8, Table 1) were placed inside a flow cell with RH control.…”
Section: Poke-flow Technique In Conjunction With Fluid Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The qualitative method of poking an inorganic particle to determine its phase (i.e., solid or liquid) was introduced by Murray et al (2012). Renbaum-Wolff et al (2013a) and Grayson et al (2015) expanded on this method by measuring the characteristic flow time of a material after poking and extracting viscosity information from simulations of fluid flow. Briefly, supermicron toluene-derived SOM particles deposited on a hydrophobic substrate (toluene 5-8, Table 1) were placed inside a flow cell with RH control.…”
Section: Poke-flow Technique In Conjunction With Fluid Simulationsmentioning
confidence: 99%
“…To determine viscosities from τ exp, flow , simulations of fluid flow were carried out with the finite-element analysis software package, COMSOL Multiphysics (Renbaum-Wolff et al, 2013a; Grayson et al, 2015). The mesh size used in the simulations was 4.04-90.9 nm.…”
Section: Poke-flow Technique In Conjunction With Fluid Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An aerosol's viscous state also has direct implications on the particle morphology, phase behaviour, optical properties, aging processes and lifetime. At the same time, only few direct measurement methods are available for monitoring such properties 1, [6][7][8][9][10][11][12][13][14][15][16] . Recently, we have demonstrated that viscosity of model organic aerosols, such as oleic acid droplets, and secondary organic aerosols (SOA) produced from the oxidation of myrcene or -pinene can be measured and imaged in a spatially and time-resolved manner using Fluorescence Lifetime Imaging Microscopy (FLIM) of molecular rotors 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Marcolli et al, 2004). 그리고 대부분의 에어로졸 성장 모델에서 에어로졸은 점성도가 낮다고 가정되어 왔다 (Hallquist et al, 2009 Bateman et al, 2015;Li et al, 2015), (2) beadmobility와 poke-flow 방법 Hinks et al, 2016;Song et al, 2016;Grayson et al, 2015;Song et al, 2015;Renbaum-Wolff et al, 2013a, b Loza et al, 2013;Perraud et al, 2012), (2) bounce 특성 이용 (Kidd et al, 2014;Saukko et al, 2012;Virtanen et al, 2010Virtanen et al, , 2011, (3) 이차유기에어로 졸의 증발률 (evaporation rate) 이용 (Cappa and Wilson, 2011;Vaden et al, 2011), (4) 이차유기에어로졸의 반응 성 (reactivity) 측정 Kuwata and Martin, 2012 n/a, n/a, n/a n/a, n/a, n/a Particle rebound Pajunoja et al (2015) α-pinene . Optical images of a SOA particle produced from isoprene photo-oxidation at 80% relative humidity at 295 K which were recorded for a bead-mobility experiment.…”
Section: 서 론mentioning
confidence: 99%